PENGARUH KOMBINASI TEKNIK PERNAPASAN BUTEYKO DAN LATIHAN BERJALAN TERHADAP KONTROL ASMA PADA PASIEN ASMA DEWASA: The Effect of Combination of Buteyko Breathing Technique And Walking Exercise on Asthma Control in Adult Asthmatic Patients - Wiwik Udayani; Muhammad Amin; Makhfudli Makhfudli (LPPM STIKES Pemkab Jombang, 2020)
ABSTRACT Introduction: Poor control of asthma can reduce the quality of life of asthma patients. Doing breathing exercises and regular physical exercise can increase asthma control. Exercises that can be done are a combination of Buteyko breathing techniques and walking exercises. The purpose of this study was to analyze the effect of a combination of Buteyko breathing techniques and walking exercises on athma control. Methods: The design of this study was quasi experimental with pretest-posttest control group design. The location of the study was in the pulmonary clinic of Regional General Hospital of Sidoarjo Regency and Bangil Regional General Hospital in Pasuruan Regency, East Java. Respondents were selected by randomization by simple random sampling. Respondents in this study amounted to 76 respondents. Asthma control were measured using Asthma Control Test. The intervention group was given a combination exercise with Buteyko breathing technique and walking exercise for 8 weeks, 3x per week, 55 minutes every training session. Giving a combination of Buteyko breathing technique and walking exercises using module and video media. Asthma control measurements were carried out 3 times (pre test, week 4, week 8). Data were analyzed using SPSS 22 with GLM-RM (General Linear Model-Repeated Measure) ANOVA. Result: The research results showed a significant difference in the astma control value between before and after 4 weeks and 8 weeks of the intervention in the treatment group with p = 0.000(p <0.05). Discussion:The combination of Buteyko breathing techniques and walking exercise increase asthma control through the mechanism of increasing CO2 and producing nitric oxide which has bronchodilation effects and through decreasing inflammatory mediators so that it can reduce asthma symptoms. This exercise can be used as an alternative choice in supporting pharmacological therapy to improve asthma control.